Potentials of Community Participation in Sustainable forestry (india) - Pathan, R. S. (Indian Forester, 1994)
Participatory forest management Initiated in india has a better chance of success, if it is in tune with socio-cultural needs of local communities. The programme, that began with restoration of forests on degraded sites, can further develop into Joint management of natural resources in important watersheds. Site specific and transparent techn-extension strategis would motivate comntunities in self governance towards sustainable development. The paper discusses necessary inputs and potentials of community participation in forset management.